New Perspectives on the Origin of the Gǝʿǝz shorter ending in the Gospel of Mark: The Coptic connection - Labadie, Damien (Apocrypha, 2023)
This paper offers an investigation into the Gǝʿǝz (Classical Ethiopic) version of the shorter ending of the Gospel of Mark. After a short introduction of the different endings in the various manuscript and linguistic traditions of the Gospel of Mark, we present a new edition of the conclusio brevior (or shorter ending) on the basis of newly discovered fourteenth- and fifteenth-century manuscripts. Then we shall attempt to unveil, through a careful comparison with the other ancient versions, the origin of the Gǝʿǝz shorter ending, suggesting a whole new theory on the subject. Indeed, we surmise that the Gǝʿǝz shorter ending was translated on a Sahidic Coptic Vorlage between the seventh and thirteenth centuries, when Ethiopia and Egypt forged renewed and strengthened relationships. Cet article propose une étude de la version guèze (ou éthiopien classique) de la conclusio brevior (ou fin brève) de l’Évangile de Marc. Après une brève introduction sur les différentes fins dans les diverses traditions manuscrites et linguistiques de l’Évangile de Marc, nous présentons une nouvelle édition de la conclusio brevior sur des manuscrits des quatorzième et quinzième siècles récemment découverts. Nous tenterons ensuite de dévoiler, par une comparaison minutieuse avec les autres versions anciennes, l’origine de la conclusio brevior guèze, en suggérant une toute nouvelle théorie sur le sujet. En effet, nous supposons que la conclusio brevior guèze a été traduite sur une Vorlage copte sahidique entre le septième et le treizième siècle, lorsque l’Éthiopie et l’Égypte renouèrent et renforcèrent leurs relations.